2012
DOI: 10.1038/tpj.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics in colorectal cancer: a genome-wide association study to predict toxicity after 5-fluorouracil or FOLFOX administration

Abstract: The development of genotyping technologies has allowed for wider screening for inherited causes of variable outcomes following drug administration. We have performed a genome-wide association study (GWAS) on 221 colorectal cancer (CRC) patients that had been treated with 5-fluorouracil (5-FU), either alone or in combination with oxaliplatin (FOLFOX). A validation set of 791 patients was also studied. Seven SNPs (rs16857540, rs2465403, rs10876844, rs10784749, rs17626122, rs7325568 and rs4243761) showed evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…In a recent study, however, P aez and colleagues investigated the association of GLI1 rs2228226 with TTR in 234 patients with stage III and high-risk stage II patients, all treated with adjuvant 5-FU-based chemotherapy, but found no clinical effect (41). Moreover, in genome-wide association studies, GLI1 rs2228226 has not been identified as a prognostic or predictive marker in colorectal cancer (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, however, P aez and colleagues investigated the association of GLI1 rs2228226 with TTR in 234 patients with stage III and high-risk stage II patients, all treated with adjuvant 5-FU-based chemotherapy, but found no clinical effect (41). Moreover, in genome-wide association studies, GLI1 rs2228226 has not been identified as a prognostic or predictive marker in colorectal cancer (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs both in common genes as MMR genes and in other novel loci as SMAD7 and MYC seem to associate with different clinical outcomes [42], or different pharmacological responses [43]. Moreover, GWAS for chromosomal 20p12.3 region, a site bereft of genes or predicted protein-encoding transcripts, suggested that particular SNP in this region could contribute to colorectal cancer progression.…”
Section: The Simultaneous Presence Of Low-risk Alleles Increases the mentioning
confidence: 99%
“…In particular, SNPs in several glutathione-S-transferase (GST) genes have been implicated in conferring resistance to Oxaliplatin. [ It is noteworthy that in a recent study by Fernandez-Rozadilla et al [63], seven SNPs (rs16857540, rs2465403, rs10876844, rs10784749, rs17626122, rs7325568, rs4243761) were found to be significantly associated with adverse drug reactions in the context of singular 5-FU or FOLFOX treatment. Given the relatively large sample size of 221 CRC patients and a validation set of 791 patients, these results hold strong statistical significance and provide potential predictive capacity for toxicity response on an individual patient basis if validated through a larger cohort.…”
Section: Markers Of Treatment Outcomes When Treated With Classical Chmentioning
confidence: 94%